Use of Calender Extract Cream in Equine Lacerate Wound - Boscarato, André Giarola; Orlandini, Carla Faria; Antunes Laginestra, Bruna de Fátima; Pacheco, Filipe Corrêa; Jardim, Giovanna Fernanda; Berta de Oliveira, João Antonio; Gazim, Zilda Cristiani; Alberton, Luiz Romulo (Acta Scientiae Veterinariae, 2020)
Background: Wounds and lacerations are constant in the clinical routine of horses. The treatment of wounds by the second intention is the most common in the equine clinic; it consists in addition to surgical debridement, the use of allopathic or phytotherapeutic healing. In this context, several phytotherapics used in folk medicine have been used with promising results in the equine species, especially marigold (Calendula officinalis L.), recognized by the German scientific committee as antiseptic and healing. The objective of this study was to evaluate the efficacy of the nonionic cream of Calendula officinalis at 2% in an extensive lacerating wound in an equine. Case: A 6-month-old female Quarter Horse, weighing 160 kg, a lacerating wound in the pectoral region of unknown traumatic origin, was treated in the large animal sector of the Veterinary Hospital of Universidade Paranaense (UNIPAR). Clinical examination revealed an exudative wound in the pectoral region, complicated by the presence of environmental organic matter and myiasis, involving transverse pectoral and descending pectoral muscles, with a large tissue separation and exposure of part of the first sternum. After an initial evaluation, a trichotomy was performed around the wound, removal of myiasis and sanitization of the wound with water and PVP-I, which was filled with sterile dressings and covered with a dressing using a tubular mesh. Antibiotic therapy was instituted, along with anti-inflammatory medication and antitetanic serum (5,000 IU). Due to the need for surgical debridement, after previous fasting and general anesthesia followed by site antisepsis, surgical debridement was performed, followed by reduction of dead space with application of standard "Wolf" sutures, for re-approximation of the wound edges was applied suture in Wolf pattern captonated with segments of equipment. In the post-surgical period, topical treatment with nitrofurazone ointment and crystal sugar was instituted. However, after five days of the surgical procedure, there was dehiscence of the wound, at which time another intervention was chosen. After sedation remaining in standard anatomical position, sutures of the same pattern and wire were applied, but captonated with polyester buds and wound dressing was instituted, followed by the application of nonionic cream of marigold (C. officinalis) extract, in the concentration of 2%, twice a day until complete healing of the wound. Discussion: The use of nonionic marigold cream (C. officinalis) 2% showed a significant efficacy, in the case reported, corroborating with literature data that marigold presented an advantage in the inflammatory phase of the healing process, when compared to the other two substances, favored epithelization and demonstrated bactericidal action. This activity is reported to the substances present in C. officinalis, especially the flavonoids, which are phenolic compounds derived from the secondary metabolism of plants. In addition to phenolic compounds such as triterpenes, faradiol esters and taraxasterol are considered responsible for antioxidant, anti-inflammatory, antimicrobial and angiogenic activities, actions that contribute directly or indirectly to the healing process. The present report contributes positively to the use of alternative treatments in wounds as the phytotherapeutic in question, since it proved feasible, besides avoiding the use of allopathic ones with higher associated costs and environmental impact in its production and use, as well as the emergence of bacterial resistance.